Lexical Errors Produced by Google Translate in Translating “Putri Serindang Bulan” to English Language - Kristiana Alasta; Iis Sujarwati (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
The purpose of this study was to analyze the lexical errors which was produced by google translate in translating “Putri Serindang Bulan” short story to English language as the target language. This study was conducted by using descriptive design with qualitatitive approach, which was done with consideration that the purpose of this research to analyze the lexical errors which produced by google translate in translating “Putri Serindang Bulan” short story to English language as the target language. This study was focused on describing the types of lexical errors produced by google translation in translating “Putri Serindang Bulan” short story to English language. In this research, the writer became the main instrument. This study obtained the data by reading “Putri Serindang Bulan” short story to understand the information of the short story, translating the “Putri Serindang Bulan” short story into English language use google translate, and then comparing the source text with the translation result to find out the translation accuracy and make the terms that were considered as inaccurate translation. The result showed that many errors were produced by google translate in translating the short story, the most frequent error found were incorrect word and missing word. In conclusion, this study suggest that the human translators must revise the translation result from machine translation.